2005
DOI: 10.1016/j.femsim.2004.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Iron and infection: the heart of the matter

Abstract: Bacterial resistance to antibiotics is a major threat to clinical medicine. However, natural resistance to bacterial infection, which does not depend on antibiotics, is a powerful protective mechanism common to all mankind. The availability of iron is the heart of the matter and the successful functioning of these antibacterial systems depends entirely upon an extremely low level of free ionic iron (10(-18) M) in normal tissue fluids. This in turn depends on well-oxygenated tissues where the oxidation-reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
214
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(224 citation statements)
references
References 26 publications
7
214
0
3
Order By: Relevance
“…Although IV iron has been theoretically implicated as a cause of increased infections. 70,71 Hoen et al 72 prospectively examined 985 dialysis patients receiving IV iron as part of the regimen for dialysisassociated anemia and found that, while central venous catheters, history of bacteremia, arteriovenous grafts, and immunosuppression were associated with increased risk of infections, ferritin levels and total dose of IV iron administration were not. Furthermore, in the Anker study, patients with heart failure (a relatively high-risk group)-including approximately 40% with CKD in a 6-month placebo-controlled trial-had improvements in quality of life and functional status without an increase in infections.…”
Section: Potential Negative Effects Of IV Ironmentioning
confidence: 99%
“…Although IV iron has been theoretically implicated as a cause of increased infections. 70,71 Hoen et al 72 prospectively examined 985 dialysis patients receiving IV iron as part of the regimen for dialysisassociated anemia and found that, while central venous catheters, history of bacteremia, arteriovenous grafts, and immunosuppression were associated with increased risk of infections, ferritin levels and total dose of IV iron administration were not. Furthermore, in the Anker study, patients with heart failure (a relatively high-risk group)-including approximately 40% with CKD in a 6-month placebo-controlled trial-had improvements in quality of life and functional status without an increase in infections.…”
Section: Potential Negative Effects Of IV Ironmentioning
confidence: 99%
“…A variety of serotypes have been identified among APEC, and strains of the same O-types (O1, 2, 4, 6, 7, 8, 16, 18 and 75) are also noticeably involved in UTIs Oelschlaeger et al, 2002;Bullen et al, 2005). The common presence of a set of virulence-associated genes among APEC and UPEC strains as well as similar disease patterns and phylogenetic background indicate a genetic relationship between APEC and UPEC isolates (Kaper et al, 2004;Moulin-Schouleur et al, 2006;Ron, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is considered to be a defense reaction depriving bacteria of iron. 13 Though mitochondrial function during sepsis and endotoxic shock has been studied extensively, results are contradictory. Mitochondrial function during septic/endotoxic shock depends on: (i) the source of mitochondria, (ii) the experimental induction of septic/endotoxic shock, and (iii) the phase of illness.…”
Section: Introductionmentioning
confidence: 99%